Asymtomatic bacteriuria in antenatal patients in Ilorin, NIgeria (2012)
Objective: To determine the prevalence of asymptomatic bacteriuria, bacteriology and sensitivity pattern in Ilorin using the gold standard of urine culture. Methods: A prospective study was carried out from 1st July to 31st October 2007, at the University of Ilorin Teaching Hospital (UITH) on 125 consenting asymptomatic pregnant women. A structured proforma was used to collect information from the women and a midstream urine specimen collected for bacteriological culture. Results: Of the 125 pregnant women, 50 had bacteriuria on urine culture giving a prevalence of 40%. The mean age of the women was 28.5 years with a standard deviation of 4.95. The age ranged between 14 and 40 years. Staphylococcus aureus was the commonest pathogen isolated (72%), followed by Proteus spp (14%). Most of the organisms showed good sensitivity to Nitrofurantoin and gentamicin. Conclusion: The prevalence of asymptomatic bacteriuria in Ilorin is high and routine urine culture is advocated for all pregnant women at booking.